Escalation of Immunosuppressive Therapy for Inflammatory Bowel Disease Is Not Associated With Adverse Outcomes After Infection With Clostridium difficile. Issue 4 (12th October 2018) - Lukin, Dana J; Lawlor, Garrett; Hudesman, David P; Durbin, Laura; Axelrad, Jordan E; Passi, Monica; Cavaliere, Kimberly; Coburn, Elliot; Loftus, Michelle; Jen, Henry; Feathers, Alexandra; Rosen, Melissa H; et al.
Abstract: Background: Clostridium difficile infection (CDI) is common in patients with inflammatory bowel disease (IBD), often leading to diagnostic confusion and delays in IBD therapy escalation. This study sought to assess outcomes after CDI in IBD patients exposed to new or escalated immunosuppressive therapy. Methods: This multicenter retrospective cohort study included IBD patients with documented CDI at 4 academic medical centers. Data were abstracted from clinical databases at each institution. Outcomes at 30 and 90 days were compared between patients undergoing new or intensified immunosuppressive therapy and those without therapy escalation. Continuous variables were compared using t tests, and proportions using chi-square tests. Multivariable logistic regression was used to determine the association of individual variables with severe outcomes (including death, sepsis, and/or colectomy) within 90 days. Secondary outcomes included CDI recurrence, rehospitalization, worsening of IBD, and severe outcomes within 30 days. Results: A total of 207 adult patients with IBD and CDI were included, of whom 62 underwent escalation to biologic or corticosteroid therapy (median time to escalation, 13 days). Severe outcomes within 90 days occurred in 21 (15.6%) nonescalated and 1 (1.8%) therapy-escalated patients. Serum albumin <2.5 mg/dL, lactate >2.2 mg/dL, intensive care unit admission, hypotension, and comorbid disease were associated with severe outcomes. Likelihood of severe outcomes was decreased in patients undergoing escalation of IBD therapy after CDI (adjusted odds ratio [aOR], 0.12) and increased among patients aged >65 years (aOR, 4.55). Conclusions: Therapy escalation for IBD within 90 days of CDI was not associated with worse clinical outcomes. Initiation of immunosuppression for active IBD may therefore be appropriate in carefully selected patients after treatment of CDI.